'PDSAFE' - a multi-dimensional model of falls-rehabilitation for people with Parkinson's. A mixed methods analysis of therapists' delivery and experience. (March 2021) - Hulbert, S; Chivers-Seymour, K; Summers, R; Lamb, S; Goodwin, V; Rochester, L; Nieuwboer, A; Rowsell, A; Ewing, S; Ashburn, A; ,
Abstract: Objective: To explore the clinical reasoning of physiotherapists using PDSAFE; according to disease severity and their experiences of treatment delivery in a large fall-prevention trial for people with Parkinson's (PwP). Design: A descriptive study of delivering PDSAFE. Semi-structured interviews explored therapists' experiences. Setting: A two-group, home-based, multi-centred, single-blinded, randomised controlled trial showed no overall effect on fall reduction between groups but demonstrated a significant secondary effect relating to disease severity with benefits to balance, falls efficacy and near-falls for all. Participants: Physiotherapists with a background in neurology and older-person rehabilitation were trained in the delivery of PDSAFE Intervention: A multi-dimensional, individually tailored and progressive, home-based programme. Results: Fifteen physiotherapists contributed to the 2587 intervention sessions from the PDSAFE trial and six of those physiotherapists took part in the interviews. The personalised intervention was reflected in the range of strategies and exercises prescribed. Most commonly prescribed fall-avoidance strategies were 'Avoiding tripping', 'Turning' and 'Freezing Cues' and all possible combinations of balance and strength training within the programme were selected. PwP with greater disease severity were more likely to have received less challenging strategies, balance and strengthening exercises than those with lower disease severity. Therapists considered the focus on fall events and fall avoidance strategies an improvement on 'impairment only' treatment. The presence of cognitive deficits, co-morbidities and dyskinesia were the most challenging aspects of delivering the intervention. Conclusion: Falls management for PwP is complex and compounded by the progressive nature of the condition. Physiotherapists both delivered and positively received PDSAFE. (248 words) The trial registration number is ISRCTN 48152791